Puccinia neovelutina nom. nov., a replaced name for Aecidium elaeagni and its new aecial host from Japan - Kakishima, Makoto; Ji, Jing-Xin; Kasuya, Taiga (Phytotaxa, 2018)
The life cycle of the aecial stage of a rust fungus found on Elaeagnus umbellata var. rotundifolia in Chiba, Japan was clarified by inoculations. This rust fungus was morphologically identified as Puccinia velutina (anamorph: Aecidium elaeagni) alternating between Carex lenta and Elaeagnus species. This plant is a new host for this rust fungus. However, the current International Code of Nomenclature (ICN, Melbourne 2012) has abolished the distinction between “anamorph” and “teleomorph” names, and we propose a new name, P. neovelutina as a replaced name for A. elaeagni, because Puccinia elaeagni is a preoccupied available name. Its epitype specimen is designated.